Borehole Electromagnetic Method for Exploration of Coal Mining Goaf - Su, Benyu; Yu, Jingcun; Sheng, Chenxing (Elektronika ir Elektrotechnika, 2016)
Due to severe harms of goaf collapse, the goaf exploration and governance has become an urgent issue for protecting the normal life of local people. According to the coal mine geology, different geo-electrical models have been employed for the purpose of discovering the goafs. However, most existing methods require a large amount of computation consumption. In order to address this issue, a forward numerical simulation using the borehole electromagnetic method has been developed in this work to explore the coal mining goafs. The innovation of this method is that the computation consuming can be saved significantly. Numerical simulation demonstrates high effectiveness of the borehole electromagnetic method in coal mining goaf exploration. Therefore, this research provides a new idea for exploring the coal mine goafs by geophysical method. DOI: http://dx.doi.org/10.5755/j01.eie.22.4.15913